RATIONALE OF INDICATORS FOR ASSESSING THE EFFECTIVENESS OF MEDICAL EXAMINATION IN THE MILITARY PERSONNEL OF THE ARMED FORCES OF THE REPUBLIC OF UZBEKISTAN - Mirrakhimova S.Sh; M.G. Mukhammedova; PhD. Ganiev B.S (Scholar Express Journals, 2024)
The article presents an assessment of the results of the sociological study of the quality of life of service members of the Armed Forces of the Republic of Uzbekistan, the power department before and after the measures to improve the organization of annual medical examination under the dispensary program. The quality of life questionnaire (QL-100), adapted by us for the contingent of servicemen of the Armed Forces of the Republic of Uzbekistan and verified by WHO experts, was used. The program on reorganization of the system of medical examination, implementation of which will significantly improve the quality of life of service members of the Armed Forces of the Republic of Uzbekistan is developed
Keywords: Medical examination; annual medical examination; quality of life